A CROSS-SECTIONAL EVALUATION OF HEAVY METAL CONTAMINATION IN RIPARIAN VEGETATION ALONG THE UMNGENI, UTHUKELA, UMVOTI, UMDLOTI, AND UMFOLOZI RIVERS, KWAZULU-NATAL. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Riparian vegetation is critical for maintaining riverine ecosystem health by filtering pollutants, stabilizing banks, and supporting biodiversity. However, increasing anthropogenic pressures, such as industrial effluent, agricultural runoff, and urban stormwater, threaten these zones. Heavy metals like lead (Pb), cadmium (Cd), zinc (Zn), and copper (Cu) can accumulate in riparian plants, posing ecological and health risks through food chain transfer. This study assessed heavy metal contamination in riparian vegetation along five major rivers in KwaZulu-Natal, South Africa. Methods A cross-sectional field study was conducted in 2024 along the uMngeni, uThukela, Umvoti, Umdloti, and Umfolozi Rivers. Three sampling sites per river (upstream, midstream, downstream) were selected based on surrounding land use and pollution sources. Dominant riparian plants, Phragmites australis, Cyperus spp., and Typha capensis, were sampled. Leaf and stem tissues were dried, ground, and digested using nitric-perchloric acid, and heavy metals were quantified via Atomic Absorption Spectrophotometry. Results were compared against international phytotoxicity thresholds and analyzed using descriptive statistics and ANOVA. Results Heavy metal concentrations varied by site and species. The uMngeni and Umvoti Rivers showed elevated Pb and Cd levels downstream of industrial zones. In contrast, the Umfolozi and Umdloti Rivers had lower concentrations within ecological safety limits. Phragmites australis exhibited higher Zn and Cu uptake, indicating phytoremediation potential. Some downstream samples exceeded phytotoxic thresholds for Pb and Cd, raising ecological and health concerns. Conclusion Riparian vegetation across KwaZulu-Natal’s rivers is accumulating heavy metals, especially near industrial and urban areas. These findings validate the role of riparian plants as bioindicators and highlight species- and site-specific risks. Recommendation Regular biomonitoring and targeted phytoremediation using high-uptake species are recommended. Efforts must also focus on pollution control and improved land-use practices to safeguard riverine ecosystems and public health.